Design and implementation of international agricultural and biological engineering expert management system based on WEB mode - Shen, Jianbo; Tan, Liwei; Wang, Yingkuan (International Journal of Agricultural and Biological Engineering, 2020)
Agriculture and biological engineering are the foundation of agricultural modernization, and related countries have also issued relevant policies to guide the development of agriculture and biotechnology. Agricultural and biological engineering experts are the intellectual resources in the field. At present, there is less research on the management and maintenance of agricultural and biological engineering experts, and there is a lack of software systems in this area. In order to realize the management and maintenance of agricultural and biological engineering expert information, a service platform for the international agricultural and biological engineering expert system based on the B/S framework has been developed. The background of the system used C# as the development language, and the foreground used JavaScript technology and Bootstrap. The software adopted ASP.NET MVC as the web development framework and used the Entity Framework to operate the SQL Server background database. The system has the function of searching and querying agricultural and biological engineering expert information according to keywords, and implements the functions of adding, deleting, and modifying data records, and the function of generating spreadsheets and importing spreadsheet data. The development of this system provides effective management tools for the maintenance and construction of agricultural and biological engineering expert databases and lays a good foundation for the construction of agricultural and biological engineering think tanks.Keywords: agricultural and bioengineering engineering, expert management, WEB mode, conditional search, think tanks, Asp.net MVC, bootstrap, entity framework technologyDOI: 10.25165/j.ijabe.20201306.5759Citation: Shen J B, Tan L W, Wang Y K. Design and implementation of international agricultural and biological engineering expert management system based on WEB mode. Int J Agric & Biol Eng, 2020; 13(6): 195–200.